The Political and Economic Conditions that Allow Politicians to Play a Role in Bullfighting in Phatthalung Province - Rakjan, Suttichai (King Prajadhipok’s Institute Journal, 2024)
This research paper focuses on the political and economic conditions that allow politicians to play a role in bullfighting in Phatthalung Province. Using qualitative research, in-depth interviews, and interview critical informants for purposive sampling. The purpose of this research is 1) to analyze the economic and political conditions that encourage politicians to play a role in bullfighting in Phatthalung Province, 2) to analyze the political relationship of the Phatthalung bullfighting network to maintain the political local vote in Phatthalung Province. Research findings show that 1) local politicians participated in the bullfighting sport because they desired to create patronage between social networks and capitalized on a large gambling economy. Furthermore, they love and personally favour bullfighting. 2) local politicians in Phatthalung Province, political relations towards maintaining the vote based on their political credibility. The bullfighting arena is considered as where local political power relates to cultural capital and leads to a patronage system. Social capital led to the creation of local political capital, resulting in local charismatic leaders. Phatthalung local politicians use political capital combined with cultural and economic capital to benefit indirectly to maintain the vote from a large number of people who are voters.